2009
DOI: 10.1186/1471-2121-10-96
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 18 attenuates estrogen receptor α-mediated signaling by sequestering LRP16 in cytoplasm

Abstract: BackgroundOncogenesis in breast cancer is often associated with excess estrogen receptor α(ERα) activation and overexpression of its coactivators. LRP16 is both an ERα target gene and an ERα coactivator, and plays a crucial role in ERα activation and proliferation of MCF-7 breast cancer cells. However, the regulation of the functional availability of this coactivator protein is not yet clear.ResultsYeast two-hybrid screening, GST pulldown and coimmunoprecipitation (CoIP) identified the cytoplasmic intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…Relative to our results, Meng et al (73) found a lower expression of cytokeratin 18 promoting proliferation of breast cancer cells MCF-7; however, they connected this effect to the modulation of estrogen receptor-α pathway. Nevertheless, SK-BR-3 cells do not express estrogen receptor-α.…”
Section: Discussioncontrasting
confidence: 99%
“…Relative to our results, Meng et al (73) found a lower expression of cytokeratin 18 promoting proliferation of breast cancer cells MCF-7; however, they connected this effect to the modulation of estrogen receptor-α pathway. Nevertheless, SK-BR-3 cells do not express estrogen receptor-α.…”
Section: Discussioncontrasting
confidence: 99%
“…Loss of CK18 expression increases the functional availability of LRP16 to ERa and promotes the proliferation of ERa-positive breast tumor cells. These findings indicate that CK18 plays an important functional role in regulating the ERa pathway (46). High-risk human papillomaviruses, such as human papillomavirus type 16 (HPV16), are the primary cause of cervical cancer.…”
Section: Interactions With Related Proteinsmentioning
confidence: 99%
“…K18 may play a regulatory role in hormonally responsive breast cancer, as it can effectively associate with and sequester the ER α target gene and ERα coactivator LRP16 in the cytoplasm, thus attenuating ERα-mediated signaling and estrogen-stimulated cell cycle progression in breast tumor cells (Meng et al , 2009). Furthermore, autophagy defects, which promote mammary tumorigenesis (Karantza-Wadsworth et al , 2007), result in K8, K17 and K19 upregulation in mouse mammary tumor cells under metabolic stress in vitro and in allograft mouse mammary tumors in vivo (Kongara et al , 2010), potentially implicating deregulation of keratin homeostasis in defective autophagy-associated breast cancer, a hypothesis worthy of further investigation.…”
Section: Keratins In Cancermentioning
confidence: 99%